GLOSSAQUA : A global dataset of size spectra across aquatic ecosystems - Zeynep Ersoy; Charlotte Evangelista; Aitor Larrañaga; Daniel M. Perkins; Javier Sánchez‐Hernández; Teofana Chonova; David Cunillera‐Montcusí; Carmen García‐Comas; Jorge García‐Girón; Ioar de Guzman; Justin Pomeranz; Victor Saito; et al. (Ecology, 2025)
Body size is a key trait in ecology due to its influence on metabolism and many other life‐history traits that affect population and community responses to environmental variation as well as ecosystem properties. The size spectrum represents the relationship between abundance (or biomass) and body size, independent of species identity. Size spectrum parameters, such as the slope or intercept, have been applied extensively as indicators of ecological status across multiple ecosystem types. The GLOSSAQUA dataset includes data from mainly heterotrophic communities composed of single (e.g., zooplankton, macroinvertebrates, or fish) to multiple taxonomic groups (e.g., from primary consumers to apex predators, and phytoplankton to large zooplankton), across diverse spatial and temporal scales, from surveys in freshwater (43% studies), marine (52% studies) and brackish (5% studies) ecosystems. In total, we compiled a unique global dataset of 8459 size spectrum slopes or exponents, 5237 intercepts, and 4,497 linearity coefficients (i.e., defined by the R 2 of the linear fit of the size spectrum) from 127 articles and gray literature (i.e., unpublished datasets). The current dataset aims to help identify the main drivers shaping aquatic size spectrum parameters at a global scale and contribute to cross‐ecosystem comparisons. GLOSSAQUA can serve to explore questions such as factors influencing spatial and temporal dynamics of community size structure, comparing the response of community size structure between natural versus human‐impacted sites, and comparing global patterns in different aquatic ecosystems. We encourage researchers, especially those from underrepresented geographical areas (e.g., South Hemisphere and Asia) to fuel this dataset in the future. The dataset is provided under a CC‐BY‐NC‐S4 4.0 license, and users are encouraged to cite this data paper when using the data.

The impacts of alien species on river bioassessment - Maria João Feio; Janine P. da Silva; Robert M. Hughes; Francisca C. Aguiar; Carlos B.M. Alves; Sebastian Birk; Marcos Callisto; Marden S. Linares; Diego R. Macedo; Paulo S. Pompeu; Wayne Robinson; Christian Schürings; et al. (Journal of Environmental Management, 2025)

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

Generation and characterisation of scalable and stable human pluripotent stem cell-derived microvascular-like endothelial cells for cardiac applications - Qasim A. Majid; Bishwa R. Ghimire; Bela Merkely; Anna M. Randi; Sian E. Harding; Virpi Talman; Gábor Földes (Angiogenesis, 2024)
Coronary microvascular disease (CMD) and its progression towards major adverse coronary events pose a significant health challenge. Accurate in vitro investigation of CMD requires a robust cell model that faithfully represents the cells within the cardiac microvasculature. Human pluripotent stem cell-derived endothelial cells (hPSC-ECs) offer great potential; however, they are traditionally derived via differentiation protocols that are not readily scalable and are not specified towards the microvasculature. Here, we report the development and comprehensive characterisation of a scalable 3D protocol enabling the generation of phenotypically stable cardiac hPSC-microvascular-like ECs (hPSC-CMVECs) and cardiac pericyte-like cells. These were derived by growing vascular organoids within 3D stirred tank bioreactors and subjecting the emerging 3D hPSC-ECs to high-concentration VEGF-A treatment (3DV). Not only did this promote phenotypic stability of the 3DV hPSC-ECs; single cell-RNA sequencing (scRNA-seq) revealed the pronounced expression of cardiac endothelial- and microvascular-associated genes. Further, the generated mural cells attained from the vascular organoid exhibited markers characteristic of cardiac pericytes. Thus, we present a suitable cell model for investigating the cardiac microvasculature as well as the endothelial-dependent and -independent mechanisms of CMD. Moreover, owing to their phenotypic stability, cardiac specificity, and high angiogenic potential, the cells described within would also be well suited for cardiac tissue engineering applications.

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Correction to: MR Imaging in Ataxias: Consensus Recommendations by the Ataxia Global Initiative Working Group on MRI Biomarkers - Gülin Öz; Sirio Cocozza; Pierre-Gilles Henry; Christophe Lenglet; Andreas Deistung; Jennifer Faber; Adam J. Schwarz; Dagmar Timmann; Koene R. A. Van Dijk; Ian H. Harding; Astrid Adarmes-Gómez; Andreas Thieme; et al. (The Cerebellum, 2023)

MR Imaging in Ataxias: Consensus Recommendations by the Ataxia Global Initiative Working Group on MRI Biomarkers - Gülin Öz; Sirio Cocozza; Pierre-Gilles Henry; Christophe Lenglet; Andreas Deistung; Jennifer Faber; Adam J. Schwarz; Dagmar Timmann; Koene R. A. Van Dijk; Ian H. Harding; Astrid Adarmes-Gomez; Andreas Thieme; et al. (The Cerebellum, 2023)
With many viable strategies in the therapeutic pipeline, upcoming clinical trials in hereditary and sporadic degenerative ataxias will benefit from non-invasive MRI biomarkers for patient stratification and the evaluation of therapies. The MRI Biomarkers Working Group of the Ataxia Global Initiative therefore devised guidelines to facilitate harmonized MRI data acquisition in clinical research and trials in ataxias. Recommendations are provided for a basic structural MRI protocol that can be used for clinical care and for an advanced multi-modal MRI protocol relevant for research and trial settings. The advanced protocol consists of modalities with demonstrated utility for tracking brain changes in degenerative ataxias and includes structural MRI, magnetic resonance spectroscopy, diffusion MRI, quantitative susceptibility mapping, and resting-state functional MRI. Acceptable ranges of acquisition parameters are provided to accommodate diverse scanner hardware in research and clinical contexts while maintaining a minimum standard of data quality. Important technical considerations in setting up an advanced multi-modal protocol are outlined, including the order of pulse sequences, and example software packages commonly used for data analysis are provided. Outcome measures most relevant for ataxias are highlighted with use cases from recent ataxia literature. Finally, to facilitate access to the recommendations by the ataxia clinical and research community, examples of datasets collected with the recommended parameters are provided and platform-specific protocols are shared via the Open Science Framework.

Wind regime changes in the Euro-Atlantic region driven by Late-Holocene Grand Solar Minima - P. Harding; C. Martin-Puertas; J. Sjolte; A. A. Walsh; R. Tjallingii; C. Langdon; S. P. E. Blockley; A. Brauer; P. Langdon; A. M. Milner; R. Muscheler; M. Perez (Climate Dynamics, 2023)

Fish and macroinvertebrate assemblages reveal extensive degradation of the world's rivers - Maria João Feio; Robert M. Hughes; Sónia R. Q. Serra; Susan J. Nichols; Ben J. Kefford; Mark Lintermans; Wayne Robinson; Oghenekaro N. Odume; Marcos Callisto; Diego R. Macedo; Jon S. Harding; Adam G. Yates; et al. (Global Change Biology, 2023)
Rivers suffer from multiple stressors acting simultaneously on their biota, but the consequences are poorly quantified at the global scale. We evaluated the biological condition of rivers globally, including the largest proportion of countries from the Global South published to date. We gathered macroinvertebrate‐ and fish‐based assessments from 72,275 and 37,676 sites, respectively, from 64 study regions across six continents and 45 nations. Because assessments were based on differing methods, different systems were consolidated into a 3‐class system: Good, Impaired, or Severely Impaired, following common guidelines. The proportion of sites in each class by study area was calculated and each region was assigned a Köppen‐Geiger climate type, Human Footprint score (addressing landscape alterations), Human Development Index (HDI) score (addressing social welfare), % rivers with good ambient water quality, % protected freshwater key biodiversity areas; and % of forest area net change rate. We found that 50% of macroinvertebrate sites and 42% of fish sites were in Good condition, whereas 21% and 29% were Severely Impaired, respectively. The poorest biological conditions occurred in Arid and Equatorial climates and the best conditions occurred in Snow climates. Severely Impaired conditions were associated (Pearson correlation coefficient) with higher HDI scores, poorer physico‐chemical water quality, and lower proportions of protected freshwater areas. Good biological conditions were associated with good water quality and increased forested areas. It is essential to implement statutory bioassessment programs in Asian, African, and South American countries, and continue them in Oceania, Europe, and North America. There is a need to invest in assessments based on fish, as there is less information globally and fish were strong indicators of degradation. Our study highlights a need to increase the extent and number of protected river catchments, preserve and restore natural forested areas in the catchments, treat wastewater discharges, and improve river connectivity.

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Benthic Invertebrate Indices Show No Response to High Nitrate-Nitrogen in Lowland Agricultural Streams - Thomas P. Moore; Catherine M. Febria; Angus R. McIntosh; Helen J. Warburton; Jon S. Harding (Water, Air, & Soil Pollution, 2021)

Trialling tools using hand‐weeding, weed mat and artificial shading to control nuisance macrophyte growth at multiple scales in small agricultural waterways - Kathryn E. Collins; Catherine M. Febria; Hayley S. Devlin; Kristy L. Hogsden; Helen J. Warburton; Brandon C. Goeller; Angus R. McIntosh; Jon S. Harding (New Zealand Journal of Marine and Freshwater Research, 2020)
Introduced aquatic macrophytes can dominate small agricultural waterways in summer and autumn becoming a significant management problem. Excessive growth can clog waterways, causing drainage issues and reducing agricultural productivity while in‐stream velocities are reduced and sedimentation increased. Consequently, water managers remove them by mechanical clearance, chemical spray and cutting which can be costly and have negative impacts on in‐stream habitat and ecological health. We trialled three tools to reduce macrophytes: hand‐weeding, weed mat and artificial shading, at a reach‐scale (50 m) and larger‐scale (200–400 m). Hand‐weeding reduced cover in the short‐term, however macrophytes recovered to pre‐treatment levels within one season. Weed mat along the banks was effective at reducing emergent macrophytes, particularly Erythranthe guttata (monkey musk) and Nasturtium microphyllum (watercress). Weed mat lasted for several growing seasons and continued to be effective. Shading over the waterway using polythene markedly reduced submerged macrophytes indicating that heavy shading by riparian plantings could reduce submerged macrophytes in the longer‐term. These results indicate that in the short‐term, weed mat could be used to limit sprawling emergent macrophytes. In the longer‐term, weed mat used in conjunction with riparian planting could provide shading so that macrophyte cover in these small waterways could be reduced and controlled.

Site Fidelity of Oyster Reef Blennies and Gobies in Saltmarsh Tidal Creeks - Juliana M. Harding; Dennis M. Allen; Eric R. Haffey; Kyle M. Hoffman (Estuaries and Coasts, 2020)

Evaluating practical macrophyte control tools on small agricultural waterways in Canterbury, New Zealand - Kathryn E. Collins; Catherine M. Febria; Helen J. Warburton; Hayley S. Devlin; Kristy L. Hogsden; Brandon C. Goeller; Angus R. McIntosh; Jon S. Harding (New Zealand Journal of Marine and Freshwater Research, 2019)
Excessive macrophytes can cause significant problems in agricultural waterways requiring active management. Conventional control techniques can have a range of adverse effects. We investigated several control tools in two experiments: firstly, we tested eight treatments at a small‐scale (2 m × 2 m). We found intensive hand weeding, weed mat and herbicide spraying to be effective treatments, reducing macrophyte cover to

Production of membrane proteins for characterisation of their pheromone-sensing and antimicrobial resistance functions - Aalishaa A. Azam; Jean M. Kinder; G. Nasir Khan; Ade Alase; Pikyee Ma; Yang Liu; James R. Ault; Peter J. F. Henderson; Babur Z. Chowdhry; Bruce D. Alexander; Stephen E. Harding; Mary K. Phillips-Jones (European Biophysics Journal, 2018)

Interaction studies of a protein and carbohydrate system using an integrated approach: a case study of the miniagrin–heparin system - Trushar R. Patel; Tabot M. D. Besong; Markus Meier; Kevin McEleney; Stephen E. Harding; Donald J. Winzor; Jörg Stetefeld (European Biophysics Journal, 2018)

Fishes in a changing world: learning from the past to promote sustainability of fish populations - T. A. C. Gordon; H. R. Harding; F. K. Clever; I. K. Davidson; W. Davison; D. W. Montgomery; R. C. Weatherhead; F. M. Windsor; J. D. Armstrong; A. Bardonnet; E. Bergman; J. R. Britton; et al. (Journal of Fish Biology, 2018)
Populations of fishes provide valuable services for billions of people, but face diverse and interacting threats that jeopardize their sustainability. Human population growth and intensifying resource use for food, water, energy and goods are compromising fish populations through a variety of mechanisms, including overfishing, habitat degradation and declines in water quality. The important challenges raised by these issues have been recognized and have led to considerable advances over past decades in managing and mitigating threats to fishes worldwide. In this review, we identify the major threats faced by fish populations alongside recent advances that are helping to address these issues. There are very significant efforts worldwide directed towards ensuring a sustainable future for the world's fishes and fisheries and those who rely on them. Although considerable challenges remain, by drawing attention to successful mitigation of threats to fish and fisheries we hope to provide the encouragement and direction that will allow these challenges to be overcome in the future.

Taxonomy of the order Mononegavirales: update 2017 - Gaya K. Amarasinghe; Yīmíng Bào; Christopher F. Basler; Sina Bavari; Martin Beer; Nicolás Bejerman; Kim R. Blasdell; Alisa Bochnowski; Thomas Briese; Alexander Bukreyev; Charles H. Calisher; Kartik Chandran; et al. (Archives of Virology, 2017)

Application of novel analytical ultracentrifuge analysis to solutions of fungal mannans - Richard B. Gillis; Gary G. Adams; David T. M. Besong; Eva Machová; Anna Ebringerová; Arthur J. Rowe; Stephen E. Harding; Trushar R. Patel (European Biophysics Journal, 2017)

Application of recent advances in hydrodynamic methods for characterising mucins in solution - Fahad M. Almutairi; Jose-Gines Hernandez Cifre; Gary G. Adams; M. Samil Kök; Alan R. Mackie; Jose Garcia de la Torre; Stephen E. Harding (European Biophysics Journal, 2016)

Scientific Bases for Numerical Chlorophyll Criteria in Chesapeake Bay - L. W. Harding; R. A. Batiuk; T. R. Fisher; C. L. Gallegos; T. C. Malone; W. D. Miller; M. R. Mulholland; H. W. Paerl; E. S. Perry; P. Tango (Estuaries and Coasts, 2014)

Trade-off in ecosystem services of the Somerset Levels and Moors wetlands - M. C. Acreman; R. J. Harding; C. Lloyd; N. P. McNamara; J. O. Mountford; D. J. Mould; B. V. Purse; M. S. Heard; C. J. Stratford; S. J. Dury (Hydrological Sciences Journal, 2011)

Temporal change in UK marine communities: trends or regime shifts? - M. Spencer; S. N. R. Birchenough; N. Mieszkowska; L. A. Robinson; S. D. Simpson; M. T. Burrows; E. Capasso; P. Cleall‐Harding; J. Crummy; C. Duck; D. Eloire; M. Frost; et al. (Marine Ecology, 2011)
A regime shift is a large, sudden, and long‐lasting change in the dynamics of an ecosystem, affecting multiple trophic levels. There are a growing number of papers that report regime shifts in marine ecosystems. However, the evidence for regime shifts is equivocal, because the methods used to detect them are not yet well developed. We have collated over 300 biological time series from seven marine regions around the UK, covering the ecosystem from phytoplankton to marine mammals. Each time series consists of annual measures of abundance for a single group of organisms over several decades. We summarised the data for each region using the first principal component, weighting either each time series or each biological component ( e.g. plankton, fish, benthos) equally. We then searched for regime shifts using Rodionov’s regime shift detection (RSD) method, which found regime shifts in the first principal component for all seven marine regions. However, there are consistent temporal trends in the data for six of the seven regions. Such trends violate the assumptions of RSD. Thus, the regime shifts detected by RSD in six of the seven regions are likely to be artefacts caused by temporal trends. We are therefore developing more appropriate time series models for both single populations and whole communities that will explicitly model temporal trends and should increase our ability to detect true regime shift events.

Structure and heterogeneity of gliadin: a hydrodynamic evaluation - Shirley Ang; Jana Kogulanathan; Gordon A. Morris; M. Samil Kök; Peter R. Shewry; Arthur S. Tatham; Gary G. Adams; Arthur J. Rowe; Stephen E. Harding (European Biophysics Journal, 2010)

A solid-state NMR study of the interaction of fish antifreeze proteins with phospholipid membranes - James Garner; Steven R. Inglis; James Hook; Frances Separovic; Margaret M. Harding (European Biophysics Journal, 2008)

Identification and sequence analysis of potyviruses infecting crops in Vietnam - C. Ha; P. Revill; R. M. Harding; M. Vu; J. L. Dale (Archives of Virology, 2008)

Design and application of two novel degenerate primer pairs for the detection and complete genomic characterization of potyviruses - C. Ha; S. Coombs; P. A. Revill; R. M. Harding; M. Vu; J. L. Dale (Archives of Virology, 2008)

CO 2 balance of boreal, temperate, and tropical forests derived from a global database - S. LUYSSAERT; I. INGLIMA; M. JUNG; A. D. RICHARDSON; M. REICHSTEIN; D. PAPALE; S. L. PIAO; E. ‐D. SCHULZE; L. WINGATE; G. MATTEUCCI; L. ARAGAO; M. AUBINET; et al. (Global Change Biology, 2007)
Terrestrial ecosystems sequester 2.1 Pg of atmospheric carbon annually. A large amount of the terrestrial sink is realized by forests. However, considerable uncertainties remain regarding the fate of this carbon over both short and long timescales. Relevant data to address these uncertainties are being collected at many sites around the world, but syntheses of these data are still sparse. To facilitate future synthesis activities, we have assembled a comprehensive global database for forest ecosystems, which includes carbon budget variables (fluxes and stocks), ecosystem traits (e.g. leaf area index, age), as well as ancillary site information such as management regime, climate, and soil characteristics. This publicly available database can be used to quantify global, regional or biome‐specific carbon budgets; to re‐examine established relationships; to test emerging hypotheses about ecosystem functioning [e.g. a constant net ecosystem production (NEP) to gross primary production (GPP) ratio]; and as benchmarks for model evaluations. In this paper, we present the first analysis of this database. We discuss the climatic influences on GPP, net primary production (NPP) and NEP and present the CO 2 balances for boreal, temperate, and tropical forest biomes based on micrometeorological, ecophysiological, and biometric flux and inventory estimates. Globally, GPP of forests benefited from higher temperatures and precipitation whereas NPP saturated above either a threshold of 1500 mm precipitation or a mean annual temperature of 10 °C. The global pattern in NEP was insensitive to climate and is hypothesized to be mainly determined by nonclimatic conditions such as successional stage, management, site history, and site disturbance. In all biomes, closing the CO 2 balance required the introduction of substantial biome‐specific closure terms. Nonclosure was taken as an indication that respiratory processes, advection, and non‐CO 2 carbon fluxes are not presently being adequately accounted for.

Mapping the 5′ ends of banana bunchy top virus gene transcripts - V. A. Herrera-Valencia; B. Dugdale; R. M. Harding; J. L. Dale (Archives of Virology, 2007)

Molecular Analysis of Fiji Disease Virus Segments 2, 4 and 7 Completes the Genome Sequence - Robert M. Harding; Parichart Burns; Robert J. Geijskes; Richard M. McQualter; James L. Dale; Grant R. Smith (Virus Genes, 2006)

Incidence and distribution of viruses of Taro ( Colocasia esculenta ) in Pacific Island countries - P. A. Revill; G. V. H. Jackson; G. J. Hafner; I. Yang; M. K. Maino; M. L. Dowling; L. C. Devitt; J. L. Dale; R. M. Harding (Australasian Plant Pathology, 2005)

Investigations into the seed and mealybug transmission of Taro bacilliform virus - A. R. Macanawai; A. A. Ebenebe; D. Hunter; L. C. Devitt; G. J. Hafner; R. M. Harding (Australasian Plant Pathology, 2005)

Sugarcane bacilliform virus encapsidates genome concatamers and does not appear to integrate into the Saccharum officinarum genome - R. J. Geijskes; K. S. Braithwaite; G. R. Smith; J. L. Dale; R. M. Harding (Archives of Virology, 2004)

Molecular analysis of Fiji disease virus genome segments 5, 6, 8 and 10 - R. B. McQualter; P. Burns; G. R. Smith; J. L. Dale; R. M. Harding (Archives of Virology, 2004)

Measurement of the skin microcirculation through intact bandages using laser Doppler flowmetry - J. M. Melhuish; L. Krishnamoorthy; T. Bethaves; M. Clark; R. J. Williams; K. G. Harding (Medical & Biological Engineering & Computing, 2004)

Analysis of variability in partial sequences of genomes of Tobacco yellow dwarf virus isolates - B. van Rijswijk; B. C. Rodoni; P. A. Revill; J. E. Thomas; J. R. Moran; R. M. Harding (Australasian Plant Pathology, 2004)

Sequence diversity of South Pacific isolates of Taro bacilliform virus and the development of a PCR-based diagnostic test - I. C. Yang; G. J. Hafner; P. A. Revill; J. L. Dale; R. M. Harding (Archives of Virology, 2003)

A promoter derived from taro bacilliform badnavirus drives strong expression in transgenic banana and tobacco plants - I. C. Yang; J. P. Iommarini; D. K. Becker; G. J. Hafner; J. L. Dale; R. M. Harding (Plant Cell Reports, 2003)

Molecular Analysis of Fiji Disease Fijivirus Genome Segments 1 and 3 - Richard B. McQualter; Grant R. Smith; James L. Dale; Robert M. Harding (Virus Genes, 2003)

Genomic characterisation of taro bacilliform virus - I. C. Yang; G. J. Hafner; J. L. Dale; R. M. Harding (Archives of Virology, 2003)

Sequence analysis of an Australian isolate of sugarcane bacilliform badnavirus - R. J. Geijskes; K. S. Braithwaite; J. L. Dale; R. M. Harding; G. R. Smith (Archives of Virology, 2002)

Surface fluxes of heat and water vapour from sites in the European Arctic - C. R. Lloyd; R. J. Harding; T. Friborg; M. Aurela (Theoretical and Applied Climatology, 2001)

Additional Rep-encoding DNAs associated with banana bunchy top virus - C. L. Horser; M. Karan; R. M. Harding; J. L. Dale (Archives of Virology, 2001)

The relationship of BRMS1 and RhoGDI2 gene expression to metastatic potential in lineage related human bladder cancer cell lines - M. Jabed Seraj; Michael A. Harding; John J. Gildea; Danny R. Welch; Dan Theodorescu (Clinical & Experimental Metastasis, 2000)

Promoters derived from banana bunchy top virus DNA-1 to −5 direct vascular-associated expression in transgenic banana ( Musa spp.) - B. Dugdale; D. K. Becker; P. R. Beetham; R. M. Harding; J. L. Dale (Plant Cell Reports, 2000)

Sequence variability in the coat protein gene of two groups of banana bunchy top isolates - R. Wanitchakorn; R. M. Harding; J. L. Dale (Archives of Virology, 2000)

Genetic transformation of Cavendish banana ( Musa spp. AAA group) cv 'Grand Nain' via microprojectile bombardment - D. K. Becker; B. Dugdale; M. K. Smith; R. M. Harding; J. L. Dale (Plant Cell Reports, 2000)

Minisatellite mutational processes reduce F st estimates - J. Flint; J. Bond; D. C. Rees; A. J. Boyce; J. M. Roberts-Thomson; L. Excoffier; J. B. Clegg; M. A. Beaumont; R. A. Nichols; R. M. Harding (Human Genetics, 1999)

Minisatellite mutational processes reduce Fst estimates - J. Flint; J. Bond; D. C. Rees; A. J. Boyce; J. M. Roberts-Thomson; L. Excoffier; J. B. Clegg; M. A. Beaumont; R. A. Nichols; R. M. Harding (Human Genetics, 1999)

Taxonomic implications for Fijiviruses based on the terminal sequences of Fiji disease fijivirus - J. A. McMahon; J. L. Dale; R. M. Harding (Archives of Virology, 1999)

Characterization and expression of the coat protein-coding region of banana bract mosaic potyvirus, development of diagnostic assays and detection of the virus in banana plants from five countries in southeast Asia - B. C. Rodoni; J. L. Dale; R. M. Harding (Archives of Virology, 1999)

Banana bunchy top virus DNA-2 to 6 are monocistronic - P. R. Beetham; R. M. Harding; J. L. Dale (Archives of Virology, 1999)

Correction - Sijun Liu; Ian D. Bedford; Peter G. Markham; Morad Ghanim; Muhamad Zeidan; Henryk Czosnek; A. Bruyère; E. Herrbach; V. Brault; V. Ziegler-Graff; H. Guilley; J. F. J. M. Heuvel; et al. (Phytoparasitica, 1998)

Sequence diversity in the coat protein coding region of twelve sugarcane mosaic potyvirus isolates from Australia, USA and South Africa - J. A. Handley; G. R. Smith; J. L. Dale; R. M. Harding (Archives of Virology, 1998)

Abstracts of presentations on plant protection issues at the xth international congress of virology - Sijun Liu; Ian D. Bedford; Peter G. Markham; Morad Ghanim; Muhamad Zeidan; Henryk Czosnek; A. Bruyère; E. Herrbach; V. Brault; V. Ziegler-Graff; H. Guilley; J. F. J. M. van den Heuvel; et al. (Phytoparasitica, 1998)

Abstracts of presentations on plant protection issues at the xth international congress of virology - E. Ramirez; A. Hernádez; E. Ham; B. L. Barrón; S. W. Ding; W. X. Li; B. J. Shi; R. H. Symons; Q. Li; K. H. Ryu; P. Palukaitis; I. B. Kaplan; et al. (Phytoparasitica, 1997)

Mapping of the gene encoding the B56β subunit of protein phosphatase 2A (PPP2R5B) to a 0.5-Mb region of chromosome 11q13 and its exclusion as a candidate gene for multiple endocrine neoplasia type 1 (MEN1) - S. A. Forbes; A. A. J. Pannett; J. H. D. Bassett; B. Harding; C. Wooding; R. V. Thakker; R. Butler; D. Ogilvie; R. Anand; P. Gaudray; G. Weber; C. Larsson; et al. (Human Genetics, 1997)

Banana bunchy top virus DNA-3encodes the viral coat protein - R. Wanitchakorn; R. M. Harding; J. L. Dale (Archives of Virology, 1997)

A trimeric, alpha-helical, coiled coil peptide: association stoichiometry and interaction strength by analytical ultracentrifugation - R. M. Thomas; A. Zampieri; K. Jumel; S. E. Harding (European Biophysics Journal, 1997)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)

A gene tree for β-globin sequences from melanesia - R. M. Harding; S. M. Fullerton; R. C. Griffiths; J. B. Clegg (Journal of Molecular Evolution, 1997)

Sequence diversity in the NIb coding region of eight sugarcane mosaic potyvirus isolates infecting sugarcane in Australia - J. A. Handley; G. R. Smith; J. L. Dale; R. M. Harding (Archives of Virology, 1996)

Expression, purification, and use as an antigen of recombinant sugarcane mosaic virus coat protein - G. R. Smith; R. Ford; J. D. Bryant; R. L. Gambley; T. K. McGhie; R. M. Harding; J. L. Dale (Archives of Virology, 1995)

Detection and characterization of pangola stunt Fijivirus from Australia using cloned cDNA probes - M. Karan; J. L. Dale; M. F. Bateson; R. M. Harding; D. S. Teakle (Archives of Virology, 1994)

Evidence that banana bunchy top virus has a multiple component genome - T. M. Burns; R. M. Harding; J. L. Dale (Archives of Virology, 1994)